(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the information attacks that can negatively affect the minds of young people in the process of globalization, as well as the issues of forming moral immunity against them. In particular, the educational opportunities of the family, the responsibility of parents, and the role of national values ​​in shaping the worldview of young people are highlighted. Also, the important role of the family environment in protecting young people from harmful information is scientifically substantiated.